Ethics of Clinical Research Involving Adults with Impaired Decision-Making Capacity - Biswas, Tonmoy (Bangladesh Journal of Bioethics, 2016)
Background: Proper decision making capacity, adequate disclosure and voluntary decisions are basic constituents of informed consent which is required in surgical procedures, any interventions, any tissue collection, or any research involving the human participants. But, it becomes more hectic if the participants or patients are physically or mentally impaired for proper understanding or rational decision making. Time has gone by assembling or regulating effective laws for research involving persons with impaired decision making capacity. Still, question arises, is it ethical to enroll an incompetent person who is not physically or mentally fit to make a decision in risky research or interventional trials? If it is, how the informed consent and ethical measures can be taken? Method: Extensive literature review was done in Google scholar, PubMed and national or institutional websites with the corresponding keywords to summarize the cases of impaired decision making and regulation of informed consent and ethical measures in those cases. Results: Decision making capacity requires three level of capacities and four levels of abilities. If a person has factual understanding, implies a certain level of rational belief, knows to manipulate information to arrive at a choice and remains stable on the choice, is known to be capacitated in decision making. Impaired decision making capacity is more common in Alzheimers disease and schizophrenia research. Although a definite line between decisional capacity and incapacity is still in question, many assessment tools are available to conclude it. Moreover, decisional incapacity has been found as a significant ratio in general or psychiatric hospitals and nursing homes regarding psychological disorders or critically ill conditions. But, these conditions should not prevent anyone from understanding, choosing, or accepting any intervention as sometimes they may have some preserved abilities too. As per accepted ethics, respect for persons incorporates at least two ethical convictions. First, the individual should be treated as an autonomous agent and second, the person with diminished autonomy is entitled to protection. Thats why, in case of severe psychiatric diseases and Alzheimers diseases, surrogate consent is recommended. But surrogacy should be reviewed by the institutional review board (IRB). Multimedia consent process, advanced consent directives, rational consent waiver and many other processes are practiced in case of ethical research involving decisional incapacitate persons which are discussed in the paper. Conclusion: It should be clarified by the IRB whether involvement of impaired subjects has beneficial scientific aim or not. Capacity assessment system should be in an organized and systemic way. Threshold for capacity and recognition of persons able to conduct this process should be fixed. Role of surrogacy and involvement of IRB to align it in a proper manner is always a matter of concern. Consideration of risk management, subjects autonomy and assent-dissent issues should be clarified in research.